1993
DOI: 10.3181/00379727-202-43511g
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreatic Polypeptide (PP-Fold) Family: Gastrointestinal, Vascular, and Feeding Behavioral Implications

Abstract: istorical Background. Of the four recognized peptide hormones secreted by the endocrine pancreas, pancreatic polypeptide (PP) was the third to be discovered, isolated, and characterized. Insulin ( 192 1-22) and glucagon ( 1923) preceded and somatostatin ( 1975) followed the isolation of PP in 1968. Despite this sequence of events-and the time interval since its discovery-PP remains somewhat of an enigma both in name and in function. The reluctance to label this polypeptide with a more descriptive title than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 38 publications
0
40
0
1
Order By: Relevance
“…Hypoglycemia, during which the muscarinic acetylcholine receptors and, to a lesser extent, adrenergic receptors are activated, also has an influence on PP release. 10 PP is released into the plasma during after-meal stimulation, in particular in the case of meals containing protein and fat. Its physiological role includes gastric stimulation inhibition, gastric acid secretion stimulation, delayed gastric emptying (Fig.…”
Section: Discussion Pancreatic Polypeptidementioning
confidence: 99%
“…Hypoglycemia, during which the muscarinic acetylcholine receptors and, to a lesser extent, adrenergic receptors are activated, also has an influence on PP release. 10 PP is released into the plasma during after-meal stimulation, in particular in the case of meals containing protein and fat. Its physiological role includes gastric stimulation inhibition, gastric acid secretion stimulation, delayed gastric emptying (Fig.…”
Section: Discussion Pancreatic Polypeptidementioning
confidence: 99%
“…For yet unexplained reasons, the islets in the uncinate process, which derives from the ventral anlage, contain more PP cells and less glucagon cells compared to the areas derived from the dorsal anlage (i.e. the body and tail of the organ) [20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…12 In humans, administration of pharmacological doses of PP has also been shown to decrease food intake over the following 24 h. 13,14 Furthermore, PP inhibits gastric emptying rate, exocrine pancreatic secretion and gallbladder motility. 15 In obese humans, studies concerning PP values have demonstrated conflicting results. Some studies found no difference between lean and obese subjects, [16][17][18] whereas other studies demonstrated lower fasting PP levels in obese subjects.…”
Section: Introductionmentioning
confidence: 99%